2022
DOI: 10.3389/adar.2022.10550
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gut Microbiota in Cannabinoid-Mediated Suppression of Inflammation

Abstract: Cannabinoids and the endocannabinoid system have been well established to play a crucial role in the regulation of the immune response. Also, emerging data from numerous investigations unravel the imperative role of gut microbiota and their metabolites in the maintenance of immune homeostasis and gut barrier integrity. In this review, we concisely report the immunosuppressive mechanisms triggered by cannabinoids, and how they are closely associated with the alterations in the gut microbiome and metabolome foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 104 publications
0
23
0
Order By: Relevance
“…A systematic review and meta-analysis has also found inconsistent results regarding cannabis’ impact on the gut microbiome across studies, highlighting the need for more comprehensive research to decipher the precise mechanisms and consequences of cannabis on gut microbiota ( 83 ). Furthermore, cannabis consumption has demonstrated potential benefits in ulcerative colitis patients, such as altering endocannabinoid tone and inducing mucosal healing, but the involvement of gut microbiota in these effects remains unclear ( 84 ). Other recreational drugs, such as cocaine and methamphetamine, have been linked to negative changes in gut microbial composition ( 85 , 86 ).…”
Section: Lifestylementioning
confidence: 99%
“…A systematic review and meta-analysis has also found inconsistent results regarding cannabis’ impact on the gut microbiome across studies, highlighting the need for more comprehensive research to decipher the precise mechanisms and consequences of cannabis on gut microbiota ( 83 ). Furthermore, cannabis consumption has demonstrated potential benefits in ulcerative colitis patients, such as altering endocannabinoid tone and inducing mucosal healing, but the involvement of gut microbiota in these effects remains unclear ( 84 ). Other recreational drugs, such as cocaine and methamphetamine, have been linked to negative changes in gut microbial composition ( 85 , 86 ).…”
Section: Lifestylementioning
confidence: 99%
“…To our knowledge, similar studies focused on MAGs have not yet been published. Considering that altered gut endocannabinoid tone and microbiome dysfunction are both associated with numerous disease states including obesity, cardiovascular diseases, metabolic dysfunction, and neurological diseases [ 14 , 24 , 35 39 ], it will be interesting to learn whether the direct effects of NAEs and other endocannabinoid-like molecules on bacterial growth contribute to the pathogenesis of these complex diseases.…”
Section: Effects On Bacterial Growth and Metabolismmentioning
confidence: 99%
“…Numerous studies have correlated compositional changes to the gut microbiome with altered host endocannabinoid tone [20][21][22][23][24][25][26][27]. These ecological changes to the microbial community are likely driven by multiple factors including the indirect effects of host cannabinoid signaling on the gut environment and the direct effects of endocannabinoids on endogenous bacteria.…”
Section: Effects On Bacterial Growth and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations